Reverse time migration based on the body-fitted grid in pseudo-acoustic vertical transverse isotropic media with non-flat surface topography - Wei, Erxiang; Huang, Jianping; Li, Zhenchun; Mu, Xinru; Li, Qingyang (Frontiers in Earth Science, 2024)
As one of the main seismic imaging methods, conventional reverse time migration (RTM) may not produce high-quality images in areas with non-flat surfaces and anisotropy because the complex surfaces have a great impact on seismic wave simulation, resulting in strong scattering waves. In addition, in isotropic acoustic (ISO) RTM, the neglection of the anisotropic effects will lead to incorrect travel times during source and receiver wavefield extrapolation. To overcome these problems, we develop a topographic pseudo-acoustic vertical transverse isotropic (VTI) RTM algorithm based on the body-fitted grid. In this method, we first derive anisotropic pseudo-acoustic wave equations in the curvilinear coordinate system. Then, the Lebedev grid finite-difference scheme is used to update these equations to simulate wavefields. Finally, we use the source-normalized cross-correlation imaging condition to realize RTM. Numerical tests are performed to evaluate the feasibility and applicability of the proposed method. The imaging results show that the proposed method can remove the effect of surface topography and anisotropy on seismic wave propagation and improve migration imaging precision.